Approaches to Assessing the Quality of Fatty Oils and Medicinal Products Formulated as Oily Solutions - A. A. Ponomarenko; L. I. Panova (Регуляторные исследования и экспертиза лекарственных средств, 2024)
INTRODUCTION. Vegetable fatty oils can comprise over 50% of a medicinal product formulated as an oily solution (in some cases, 100%). The quality of the vegetable fatty oil used and the processes occurring in this oil have a significant impact on the quality of the medicinal product. The factors that influence the formation of impurities in vegetable fatty oils include the manufacturing process and storage and transportation conditions. Therefore, it is necessary to analyse national and international approaches to the assessment of impurities in vegetable fatty oils and medicinal products based on vegetable fatty oils.AIM. This study aimed to analyse pharmacopoeial requirements for the control of impurities in vegetable fatty oils and summarise these requirements as recommendations for manufacturers of oily solution formulations containing 50–100% of vegetable fatty oils.DISCUSSION. This study compared the requirements of national and international pharmacopoeias (State Pharmacopoeia of the Russian Federation, European Pharmacopoeia, and United States Pharmacopeia) for the control of impurities in vegetable fatty oils. The comparative analysis focused on the vegetable fatty oils most frequently used as solvents for the production of liquid dosage forms (sesame, olive, sunflower, soya-bean, rapeseed, and castor oils) as a case study. According to the results, as a rule, the impurity profiles provided by the monographs of the leading international pharmacopoeias for the same vegetable fatty oils differ, either qualitatively or quantitatively, and depend on the type of oil. Additionally, the pharmacopoeial limits for impurities in vegetable fatty oils vary depending on the intended dosage form. The State Pharmacopoeia of the Russian Federation lacks individual monographs for some of the vegetable fatty oils most frequently used in the production of medicinal products (sunflower, olive, sesame, and rapeseed oils). The State Pharmacopoeia of the Russian Federation requires that the quality of these oils should be assessed using the general approach described in the general monograph Vegetable fatty oils, whereas the requirements for the quality of medicinal products formulated as oily solutions are provided exclusively in the general monograph Solutions, which includes the acid value and peroxide value tests.CONCLUSIONS. To draft pharmacopoeial monographs for oily solution formulations, it is necessary to standardise approaches to assessing impurities, in particular, to provide for mandatory acid value and peroxide value testing, as these attributes characterise the quality of oils during both production and storage.